Twin texts: a possibility to involve children in inquiry-oriented processes - Becerra Camargo, Claudia Yolanda (Colombian Applied Linguistics Journal, 2006)
This article reports on the experience I lived while implementing the instructional design of my Master thesis. The research proposal I am currently carrying out is primarily concerned about conflict resolution and cooperative learning in the English classroom. The proposal was developed in a public primary school in Ciudad Bolivar, Bogotá, Colombia. Besides, my participants were a group of fourth graders. The methodology used during the implementation had to do with: cooperative learning, in which learning implies co-construction. The authoring cycle that is an option for involving students in inquiry processes, and twin texts, understood as the use of two books (one fictional & one non-fictional) related to the same topic but from different perspectives. The three elements described above were interwoven along the process. To conclude, this experience helped me to recognize certain aspects regarding my professional practices: first, the importance of innovation. Second, the value of other teacher-researchers’ experiences and insights. Third, to recognize our students as owners of their learning process. Fourth, how the authoring cycle promoted cooperative learning and decreased conflicts. Finally and foremost, the value of literature as a powerful language learning resource.